1999
DOI: 10.1016/s0006-3495(99)77078-5
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model of Circadian Rhythms Based on Dimerization and Proteolysis of PER and TIM

Abstract: Many organisms display rhythms of physiology and behavior that are entrained to the 24-h cycle of light and darkness prevailing on Earth. Under constant conditions of illumination and temperature, these internal biological rhythms persist with a period close to 1 day ("circadian"), but it is usually not exactly 24h. Recent discoveries have uncovered stunning similarities among the molecular circuitries of circadian clocks in mice, fruit flies, and bread molds. A consensus picture is coming into focus around tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
212
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(225 citation statements)
references
References 40 publications
(61 reference statements)
11
212
2
Order By: Relevance
“…As we show in the Supplementary Methods and Supplementary Discussion, discretenessinduced inversion effects also exist in the protein concentration output of a gene regulation network with negative feedback (Supplementary Figs S1 and S2). This motif is ubiquitous in biology, appearing in such diverse contexts as metabolism 38 , signalling 39 , somitogenesis 40 , and circadian clocks 41 . In biological systems, the gene network considered feeds into more complicated metabolic or signal-transduction networks, and it is plausible that the discreteness-induced concentration inversions at the level of the gene network are propagated into these downstream networks.…”
Section: Discussionmentioning
confidence: 99%
“…As we show in the Supplementary Methods and Supplementary Discussion, discretenessinduced inversion effects also exist in the protein concentration output of a gene regulation network with negative feedback (Supplementary Figs S1 and S2). This motif is ubiquitous in biology, appearing in such diverse contexts as metabolism 38 , signalling 39 , somitogenesis 40 , and circadian clocks 41 . In biological systems, the gene network considered feeds into more complicated metabolic or signal-transduction networks, and it is plausible that the discreteness-induced concentration inversions at the level of the gene network are propagated into these downstream networks.…”
Section: Discussionmentioning
confidence: 99%
“…Hill coefficient of more than one was used to describe the activation of per expression by CLK or repression of per expression by PER to create oscillations, whereas in some models it was found that oscillations were preserved with a Hill coefficient of one if other parameters were properly chosen (Leloup and Goldbeter 1998;Tyson, Hong et al 1999;Kurosawa, Mochizuki et al 2002). Finally, we would like to make some comparisons with two previous models as the core mechanisms of these models are similar (Smolen, Hardin et al 2004;Ruoff, Christensen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, it has been shown experimentally that light enhances degradation of TIM, and consequently degradation of TIM in the light alters the level of other clock components and, thus, resets of phase of a oscillator (Zeng, Qian et al 1996). In terms of modelling, increase in TIM degradation rate has been used to model light response and entrainment to LD cycles in some previous models (Leloup and Goldbeter 1998;Tyson, Hong et al 1999). As TIM stabilises PER in the cytoplasm, the indirect effect of light is to regulate the localisation of PER and in turn to decrease the PER level in the nucleus.…”
Section: Response Of the Circadian Clock To Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in striking contrast to research on circadian rhythms, which has a large and rapidly growing literature of models that span the metazoans (Forger and Peskin, 2003;Leise and Siegelmann, 2006;Nakajima et al, 2005;Tyson et al, 1999). The difference is largely due to the ubiquity of circadian rhythms, in particular their presence in several invertebrate and vertebrate model organisms including mammals (Dunlap and Loros, 2004;Hardin, 2005;K.…”
Section: Introductionmentioning
confidence: 89%